TEACHER STRATEGIES IN FACING IN THE CHALLENGES OF 21st CENTURY EDUCATION - Ileena Ramadhanti (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2023)
Education in the 21st century faces complex challenges, especially in the context of shifting paradigms toward modern education. This article outlines the definition of education as a conscious effort to develop spiritual potential, self-control, personality, intelligence, noble character, and necessary skills. The paradigm shift in 21st-century education requires teachers to adapt to the developments of the times, particularly in the implementation of suitable educational strategies. Challenges for 21st-century teachers involve aspects of technology, multiculturalism, active learning, and accountability. Teachers must overcome technological gaps, confront changes in teaching methods, and meet the demands of 21st-century skills. This research aims to understand teacher strategies in facing the challenges of 21st-century education using a qualitative descriptive analysis approach. The research findings indicate that teachers employ strategies such as collaborative learning, blended learning, project-based learning, problem-based learning, design-based learning, and inquiry-based learning. These strategies aim to enhance 4C skills (communication, collaboration, creativity, and critical thinking) essential for meeting the demands of the 21st century. By implementing these strategies, teachers can overcome challenges and prepare students for a future full of change and complexity.